Crystal structure of blue laccase BP76, a unique termite suicidal defense weapon - Škerlová, Jana; Brynda, Jiří; Šobotník, Jan; Zákopčaník, Marek; Novák, Petr; Bourguignon, Thomas; Sillam-Dussès, David; Řezáčová, Pavlína (Structure (London, England, 2024)
Aging workers of the termite Neocapritermes taracua can defend their colony by sacrificing themselves by body rupture, mixing the externally stored blue laccase BP76 with hydroquinones to produce a sticky liquid rich in toxic benzoquinones. Here, we describe the crystal structure of BP76 isolated from N. taracua in its native form. The structure reveals several stabilization strategies, including compact folding, glycosylation, and flexible loops with disulfide bridges and tight dimer interface. The remarkable stability of BP76 maintains its catalytic activity in solid state during the lifespan of N. taracua workers, providing old workers with an efficient defensive weapon to protect their colony.
Keywords: Models, Molecular; Protein Multimerization; Catalytic Domain; multimerizace proteinu; hmyzí proteiny; krystalografie rentgenová; Neocapritermes taracua; Crystallography, X-Ray; Isoptera; zvířata; molekulární modely; colony defence; Protein Folding; Amino Acid Sequence; lakasa; laccase; protein stabilization; glykosylace; autothysis; sbalování proteinů; katalytická doména; insect glycosylation; Laccase; single-wavelength anomalous diffraction; Animals; X-ray crystallography; Glycosylation; Insect Proteins; benzoquinone; sekvence aminokyselin